On the smoothness of a generalized solution of the first initial boundary-value problem for strongly parabolic systems in a cylinder with nonsmooth base with respect to time variable - Nguyen Manh Hung; Pham Trieu Duong (Український математичний журнал, 2004)
We consider the first initial boundary-value problem for strongly parabolic systems in an infinite cylinder with nonsmooth boundary. We establish conditions for the existence of generalized solutions, an estimate for this solutions, and an estimate for the derivative of the solution. Досліджується перша початкова крайопа задача для сильно параболічних систем Ііа нескінченному циліндрі з негладкою межею. Встановлено умови існування узагальненого розв'язку та його оцінку, а також оцінку похідної розв'язку.